Lipin-1 Deficiency-Associated Recurrent Rhabdomyolysis and Exercise-Induced Myalgia Persisting into Adulthood: A Case Report and Review of Literature - Neluwa Liyanage Ruwan Indika; Dinesha Maduri Vidanapathirana; Eresha Jasinge; Roshitha Waduge; Narangoda Liyanage Ajantha Shyamali; Poruthotage Pradeep Rasika Perera (Case Reports in Medicine)
Phosphatidate phosphatase-1 (lipin-1) is encoded by LPIN1 gene. Lipin-1 deficiency has been reported as the second most common cause of early-onset rhabdomyolysis after primary fatty acid oxidation disorders. We report a case of a 32-year-old Sri Lankan female with a history of more than 10 episodes of rhabdomyolysis and exercise intolerance since childhood. These episodes were triggered by infections and exercise. A temporal relationship between the acute episodes and use of drugs such as theophylline, mefenamic acid, co-trimoxazole, and combined oral contraceptive pills was also noted. There was marked elevation of serum creatine kinase and transaminases during acute episodes. Family history revealed parental consanguinity and an affected sibling who died of an acute episode associated with muscle weakness, dark coloured urine, and cyanosis, at the age of 2 years. The histochemical findings of the patient under discussion were consistent with a metabolic myopathy affecting membrane integrity. A homozygous, likely pathogenic variant c.1684G>T encoding p.(Glu562∗) was identified by clinical exome sequencing. Even though the studies to date give no convincing evidence of a possible causal or contributory relationship between the drugs under discussion and lipin-1 related rhabdomyolysis, this case highlights the importance of pharmacovigilance and reporting adverse drug reactions in patients with lipin-1 deficiency.